People of peace : 40 inspiring icons - Mirza, Sandrine; Le Duo (Firm) (Minneapolis, MN : Wide Eyed Editions, 2018)
Profiles peace activists through history including Sophi Scholl, Martin Luther King, Wangari Maathai, Nelson Mandela, and Malala Yousafzai.
7.5
3-6.
3-6
Keywords: Pacifists; Pacifists